Family Nursing Care with Asthma Education Using The Calgary Family Assessment Model (CFAM) and The Calgary Family Intervention Model (CFIM): Case Report - Azizah, Neng Zihan Nurul; Purnama, Dadang; Lukman, Mamat (Journal of Nursing Care, 2026)
Asthma is a chronic respiratory disease that can be triggered by hereditary and environmental factors, such as exposure to cigarette smoke at home. Effective asthma management requires active family involvement in the care process. This study aims to identify nursing problems and provide interventions for families with a history of asthma using the Calgary Family Assessment Model (CFAM) approach, which consists of the dimensions of Structural Assessment, Developmental Assessment, and Functional Assessment. Meanwhile, the Calgary Family Intervention Model (CFIM) focuses on three main domains of Cognitive, Affective, and Behavioral change as a conceptual framework. The research method used is descriptive with a case study design and the subjects in this study were one family with hereditary asthma selected using purposive sampling. This study was conducted from December 31, 2024, to January 22, 2025. The assessment was conducted for 15-30 minutes using the CFAM approach, which includes structural, developmental, and functional components of the family. The intervention was conducted using the CFAM approach across three domains: cognitive (education), affective (emotional counseling), and behavioral (lifestyle modification). The intervention involved education using easy-to-understand language and illustrated leaflets. Evaluation results showed increased family knowledge about asthma and the dangers of smoking, improved communication among family members, and a decrease in smoking frequency from six to three cigarettes per day. These findings suggest that implementing the CFAM and CFIM concepts can improve family health knowledge and support healthier behavior changes. This study recommends broader use of the CFAM and CFIM concepts in community-based family nursing practice.